Impact of Spread Effect on Public Market Place (Lambaro Aceh Besar) - Armalia, Armalia; Fadhly, Noer; Zukhrina Oktaviani, Cut (Journal of World Science, 2023)
Aceh Besar Regency is the primary access and entrance gate to the provincial capital, directly adjacent to the city of Banda Aceh. This proximity positions Aceh Besar as a buffer from the city. The strategic location and position make Aceh Besar an opportune area for rapid growth and development. Thus, developing these strategic areas will foster the emergence of growth centers (Growth Poles). This research aims to determine and analyze the impact of the spread effect on the public market between Aceh Besar Regency and Banda Aceh City as a potential sector that can encourage economic growth and have a spreading effect on the surrounding area. The analysis method employed in this research is a quantitative approach utilizing descriptive analysis. The results of the research show that the results of the gravity analysis of sub-districts in Aceh Besar Regency and Banda Aceh City show that Want Jaya Sub-district as the primary growth center has the greatest interaction value with Darul Imarah Sub-district. The last sub-district is one of the sub-districts in Aceh Besar Regency with an interaction value of 76,525,776,000. Furthermore, the largest interaction values after Darul Imarah District are Krueng Barona Jaya District and Montasik District with interaction values of 15,062,514,047 and 11,831,506,347 respectively.